Hydrocracking And Hydrodesulphurization Activities Of Nimo Catalyst Supported On Alumina And Activated Carbons For Petroleum - Ahmed Alsobaai, Ahmed Mubarak (2003)
This study aims to improve petroleum residual oil quality by converting it into lighter products over different types of catalysts. The process was conducted in a batch mode under various operating conditions, temperature in range 250-350 °C, reaction time 90- 230 min and catalyst ratio 0.3-1.30 using a high-pressure stirred reactor in the presence of hydrogen and catalyst. At first commercial NiMo/Ah03 catalyst was used to find the range of operation conditions for catalytic hydrocracking of petroleum residual oi). Statistical design of experiment, (DOE), was used to obtain the range of operating conditions. It was found that the range of operating conditions for catalytic hydrocracking of petroleum residual oil over commercial NiMo/Ah03 sulphided catalyst are: temperature of 330°C, time of 200 min and catalyst ratio of 1.1.